HUBUNGAN PERBANDINGAN SOSIAL DI MEDIA SOSIAL DAN SELF-COMPASSION PADA DEWASA AWAL - Sutiawan Sutiawan; Roswiyani Roswiyani (STKIP Subang, 2026)
Emerging adulthood is a developmental phase particularly vulnerable to mental health risk, partly driven by the intensity of social comparison on social media. This study aimed to examine the relationship between social comparison on social media and self-compassion among emerging adults. A quantitative correlational design with purposive sampling was employed, involving 377 emerging adults aged 18-25 years residing in the Greater Jakarta area (Jabodetabek) who actively use social media. Social comparison was measured using the Iowa-Netherlands Comparison Orientation Measure (INCOM) adapted by Fuad (2023), while self-compassion was measured using the Indonesian Self-Compassion Scale (SWD) adapted by Sugianto et al. (2020). Because the residual data were not normally distributed based on the Kolmogorov-Smirnov test, hypothesis testing was conducted using Spearman's Rho non-parametric correlation. Results showed a significant, strong negative relationship between social comparison and self-compassion (r = -.731; p = .000). Social comparison correlated strongly and negatively with all positive dimensions of self-compassion, the strongest being common humanity (r = -.663), and positively with all its negative dimensions, the strongest being self-judgment (r = .616). Significant differences in social comparison were found by gender, and in self-compassion by daily social media use duration. These findings underscore the importance of self-compassion-based psychological interventions to reduce the negative impact of social comparison among emerging-adult social media users.